Death Receptors DR4 and DR5 Undergo Spontaneous and Ligand-Mediated Endocytosis and Recycling Regardless of the Sensitivity of Cancer Cells to TRAIL - Artykov, Artem A.; Yagolovich, Anne V.; Dolgikh, Dmitry A.; Kirpichnikov, Mikhail P.; Trushina, Daria B.; Gasparian, Marine E. (Frontiers in Cell and Developmental Biology, 2021)
TRAIL induces apoptosis through the death receptors (DRs) 4 and 5 expressed on the cell surface. Upon ligand stimulation, death receptors are rapidly internalized through clathrin-dependent and -independent mechanisms. However, there have been conflicting data on the role of death receptor endocytosis in apoptotic TRAIL signaling and possible cell type-specific differences in TRAIL signaling have been proposed. Here we have compared the kinetics of TRAIL-mediated internalization and subsequent recycling of DR4 and DR5 in resistant (HT-29 and A549) and sensitive (HCT116 and Jurkat) tumor cell lines of various origin. TRAIL stimulated the internalization of both receptors in a concentration-dependent manner with similar kinetics in sensitive and resistant cell lines without affecting the steady-state expression of DR4 and DR5 in cell lysates. Using the receptor-selective TRAIL variant DR5-B, we have shown that DR5 is internalized independently of DR4 receptor. After internalization and elimination of TRAIL from culture medium, the receptors slowly return to the plasma membrane. Within 4 h in resistant or 6 h in sensitive cells, the surface expression of receptors was completely restored. Recovery of receptors occurred both from newly synthesized molecules or from trans-Golgi network, as cycloheximide and brefeldin A inhibited this process. These agents also suppressed the expression of cell surface receptors in a time- and concentration-dependent manner, indicating that DRs undergo constitutive endocytosis. Inhibition of receptor endocytosis by sucrose led to sensitization of resistant cells to TRAIL and to an increase in its cytotoxic activity against sensitive cells. Our results confirm the universal nature of TRAIL-induced death receptor endocytosis, thus cell sensitivity to TRAIL can be associated with post-endocytic events.